Evaluation of Nursing Profession within The Scope of professionalazation in Turkey and The Process of Harmonization to The European Union: A Qualitative Study - Bilgen Özlük; Haydar Sur (Association of Nurse Managers, 2017)
INTRODUCTION: Professionalism is a concept that emphasizes occupational values and commitment. Profession professionalism is a significant phenomenon which has roles in establishing the standards of the occupation and providing high quality care. This study was conducted with the purpose of investigating professionalization of the occupation of nursing in Turkey and the European Union (EU) harmonization process. METHODS: While the study is a qualitative one, purposive sampling was used. Study group of research consisted of total 15 person faculty members from nursing departments of universities in Turkey, nursing services managers of hospitals and EU experts. The data were collected using the semi-structured in-depth interview method. RESULTS: It was determined that: nursing is not yet seen as an occupation in Turkey based on criteria of professionalism; fundamental problems in professionalization of the occupation are the variety of occupational education levels, differences seen in types of employment, and low levels of occupational autonomy and organization, and EU criteria will have positive effects as a driving force on the development of professionalization in the occupation of nursing. DISCUSSION AND CONCLUSION: In conclusion, it was established that the professionalization process of the occupation of nursing is still in progress in Turkey, and EU harmonization standards will be a driving force to accelerate this progress.